PENYUSUNAN INSTRUMEN TES TENGAH SEMESTER GENAP FISIKA X SMA UNTUK KELAS X SMA - Wahyu Nur Ivanty, Dian; Siti Aminah, Nonoh; Yusliana Ekawati, Elvin (Jurnal Pendidikan Fisika, 2013)
The aim of this research was to apprehend the characteristics of physics mid semester test instrument which has been arranged. Research method used bydescriptive method.Â  Procedures used are adopt the procedure of arranging the test by Djemari Mardapi. Its use qualitative analysis technique which consists of aspect materials, construction, and language, and quantitative analysis using the program MicroCat ItemanÂ  version 3.00 to determine difficulty level, determinant indeks and effectiveness of detractors. The results of the test arrangement was an objective test in multiple choices form with five answer choices of 40 items. Time allocation of test doing was 90 minutes. Characteristics of final arranged test are: 1) difficulity level: 42,5% medium category and 57,5% difficult category; 2) determinant indeks: 5% excellent category, 35% good category, 25% satisfactory category, 27,5% poor catagory dan 7,5% very poor; 3)effectiveness of detractors: 95% four distractors functioned, dan 5% tri distractors functioned. The final result is about 60% received and 40% revised. Key word: Test arrangement, difficulty level, determinant indeks and effectiveness of detractors